PERBEDAAN SIKLUS MENSTRUASI ANTARA AKSEPTOR KB SUNTIK 1 BULAN DAN AKSEPTOR KB SUNTIK 3 BULAN DI BPM NY. “S” DESA KLUWIH KECAMATAN TULAKAN KABUPATEN PACITAN - Murniati Murniati; Astrilinda Cahya Putri (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2019)
Menstruation is regular bleeding from the uterus as a sign that the uterus hasfulfilled its function. Based on preliminary data through interviews on long term acceptorKB 3 month injection and long term acceptor KB injection 1 month on 25 November 2016which amounted to 20 people in BPM Ny